Evaluasi Pemberian Obat Diminazene Aceturate Secara In Vivo Pada Mencit (Mus musculus) yang Diinfeksi Isolat Trypanosoma evansi - Reza Yesica; Bambang Sutrisno; Wisnu Nurcahyo (Jurnal Sain Veteriner, 2021)
Abstract Surra's disease is caused by Trypanosoma evansi parasite has been established as one of the strategic infectious animal diseases. Drug resistance in this case is one of the major challenges in handle and control them. The aim of this study is to evaluate the provision drug resistance diminazene aceturate (Tryponil®) on Trypanosoma evansi isolate from Pemalang and Brebes Central Java province with in vivo test in mice. Total 50 mice, BALB / c strain, male, 2 months, body weight ± 30 gram are obtained from LPPT-UGM, adapted for one week. Mice were divided into 10 groups consist of 5 each. Each mouse was infected with Trypanosoma evansi by intraperitonial route. Treatment was given when mice had reached the level of parasitemia 108 – 109 trypanosoma / mL of blood this was predicted 24 hours post-infection (Eisler et al., 2001). The administration of the drug tryapanosidal was done intraperitonial with doses 1mg/kg, 3mg / kg, 5 mg / kg and 7mg / kg. Observation of parasitemia did every 2 times in one week till 60 days of observation. Parasitemia observation was performed using 3 techniques. The first method was native examination used a microscope, if the negative results would be followed by MHCT (Microhaematocrit centrifugation Technique) and BCT (Buffy Coat Technique) according to OIE (2012). Data obtained from the treatment group were the level of parasitemia, the number of deaths and the number of live mice from each test dose. The results are analysed by standard logit or probit. The results of this study showed the effects of the drug Dimianzene aceturate on both isolates varied. On Brebes Isolate was effective at doses of 7 mg / kg BW (100%) and 5mg / kg BW (80%), whereas in the effective dose Pemalang isolate at 3 mg dose / kg BW (80%), 5 and 7 mg / kg BW (100%). While at the lowest dose of 1 mg / kg obtained a level of effectiveness of 0% in both isolates. It could be concluded that both isolates have different pathogens and indicate resistance subpopulation to diminazene aceturate.Keywords : diminazene aceturate, in vivo, resistance, Trypanosoma evansi.